2018
DOI: 10.1039/c7ta11051k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystal phase and composition on structurally ordered Pt–Co–Ni/C ternary intermetallic electrocatalysts for the formic acid oxidation reaction

Abstract: An ordered structure and multiple components in combination promote enhanced activity and stability of Pt-based catalysts toward the FAOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 55 publications
5
55
0
Order By: Relevance
“…In the case of Pt–M (1:1) compounds, the transition from a disordered to an ordered phase occurs together with a change in the crystal structure, from an fcc structure to either an fct structure for PtM (M = Fe, Ni, Zn, and Cd) and PtNi 0.5 Co 0.5 catalysts, a body‐centered tetragonal (bct) structure for PtZn, or a mixed hexagonal close‐packed/cubic close‐packed (hcp/ccp) structure for PtAg . The disordered–ordered phase transition takes place by heat treatment at high temperature.…”
Section: Activity Of Binary Pt–m (M = 1st and 2nd Row Transition Metamentioning
confidence: 99%
“…In the case of Pt–M (1:1) compounds, the transition from a disordered to an ordered phase occurs together with a change in the crystal structure, from an fcc structure to either an fct structure for PtM (M = Fe, Ni, Zn, and Cd) and PtNi 0.5 Co 0.5 catalysts, a body‐centered tetragonal (bct) structure for PtZn, or a mixed hexagonal close‐packed/cubic close‐packed (hcp/ccp) structure for PtAg . The disordered–ordered phase transition takes place by heat treatment at high temperature.…”
Section: Activity Of Binary Pt–m (M = 1st and 2nd Row Transition Metamentioning
confidence: 99%
“…[17] Inspired by these results, variousc ombinations of platinum-based trimetallic electrocatalysts, such as PtMN (M,N= Pd, Au, Ru, Ir,N i, Co, Fe, Cu, Mn), have been synthesized, which show highelectrocatalytic activities. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Surface structure engineering represents another powerful avenue to tune and boost the catalytic performance of platinum and platinum-based catalysts. [3,33,34] In this regard, much attention has recently been paid to the synthesiso fv arious platinum-based nanomaterialsw ith different morphologies and structures, such as nanowires, [27] nanorods, [35][36][37] nanocubes, [38,39] and nanodendrities.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations based on the diffraction peak widths by the Debye‐Scherrer equation, and the domain size of PdCuFe/C‐500 is larger than that of PdCuFe/C‐400. Therefore, we concluded that increasing the annealing temperature not only promotes the conversion from the disordered into the ordered phase, but also increases the crystal size . The sizes of the nanoparticles are shown in Table S1.…”
Section: Resultsmentioning
confidence: 84%
“…Hence, compared with disordered alloy, the stronger geometric effects and electronic effects on intermetallic could changes the surface coordination of the active site. The change of the catalytic active site can cause the d‐band center shift and change adsorbate interacts interactions, which make them exhibiting higher catalytic performance . At the same time, the intermetallic compound has a lower negative entropy and stronger electronic interaction than the alloy.…”
Section: Introductionmentioning
confidence: 99%